Dinophysiales (Dinophyceae) of the National Park Sistema Arrecifal Veracruzano, Gulf of Mexico, with a key for indentification - Okolodkov, Yuri B. (Instituto de Ecología, A.C., 2014)
The morphology of 38 species from eight genera of the order Dinophysiales was studied based on about seven hundred 20 μm phytoplankton net samples taken from May 2005 through April 2008 at 27 sampling stations in the National Park Sistema Arrecifal Veracruzano, southwestern Gulf of Mexico. Short descriptions and synonyms are given for each species. Cell size variation with the mean and the standard deviation are given for most species. Twenty-three species are provided with affinities and morphological, taxonomic and nomenclatural comments. Dichotomous keys for identification of the genera and species of Amphisolenia (4 species), Dinophysis (7), Heteroschisma (1), Histioneis (6), Ornithocercus (7), Phalacroma (9), Pseudophalacroma (1) and Sinophysis (3) are presented, and species are illustrated with light and scanning electron microscope photographs and line drawings. Phalacroma equalanti (Balech) Okolodkov comb. nov. is established. Thirteen species are new records for the State of Veracruz, and Histioneis isseli and Pseudophalacroma nasutum are new for the Gulf of Mexico.